IMPROVING EUTROPHICATION REGULATION OF WATER BODIES BY USING BIOLOGICAL METHODS - Pysarenko, P. V.; Samoilik, M. S.; Dychenko, O. Yu.; Sereda, M. S.; Korchahin О. Р. (Scientific Progress & Innovations, 2021)
The conducted study is a complex analysis of the influence of waters having different eutrophication level on the similarity, growth and root system of sown seeds. To estimate the phototoxic effect, the following indicators were used in the experiment: plantlets’ height, roots’ length, as well as the phyto-mass of plantlets and plant root system. The following plants having highly expressed stress-reaction on pollution were used as test ones: Pisum sativum, Triticum aestivum, Lepidium sativum. The phytotoxic effect is considered significant if it makes more than 20%. The possibility of using probiotics to fight the process of “water bloom” was studied. The assessment of phytotoxic effect of the examined water samples before and after their purifying with Sviteco-Agrobiotic-01 probiotic (in 1 : 100 solution) as to germinating capacity, growth, and root system of the sown seeds was conducted. It has been determined that after purifying with probiotics, all the water samples concerning Triticum aestivum and Lepidium sativum biometric indicators were regarded nontoxic (the toxicity was absent); moreover, clear dynamics to increasing the purification effect at impurities’ concentration increase in the water was registered. As a result of the study, the effectiveness of applying probiotic preparations to decrease water phyto-toxicity has been established, that enables to suppose the possibility of regulating the processes of surface waters’ eutrophication by using probiotics. In order to assess the effectiveness of applying probiotic preparations to regulate water systems’ eutrophication, the study of water samples before and after purification was conducted by chemical indicators. It has been established that Sviteco-Agrobiotic-01 had the highest effect as to the majority of substances. Moreover, the effectiveness of purification was the following: by BOD5– 39 %, COD – 33 %, suspended matters – 18 %, ammonium nitrogen – 33 %, manganese – 20 %. It has been found that the use of probiotic preparations is more effective in comparison with chemical methods; in particular, the application of Sviteco-Agrobiotic-01 probiotic eliminates 70–80 % of cyanobacteria. The same result was obtained while using potassium permanganate, but the negative effect of this method is the fact that the use of chemical methods leads to repeated water bodies’ pollution. Our study proves the possibility for developing complex systems of surface water bodies’ purification with environmentally safe methods to prevent water reservoirs’ bloom, which is one of the priorities in the development of urbanized areas and sustainable development of the society.